Cobalt-Catalyzed Cycloisomerization of N,N-Diallylanilines - Liu, Jun; Yang, Zhanhui; Zheng, Minfang; Wu, Hongfei; Chen, Ning; Xu, Jiaxi (Synthesis, 2019)
Cobalt catalysts bearing 2-imino-1,10-phenanthroline ligands are quite efficient bench-stable catalysts for the oligomerization of ethylenes. Herein, their further application was developed in the catalytic transformation of N,N-diallylanilines to pyrrolidines through a cycloisomerization process. In this protocol, chlorobenzene is a vital additive to promote reaction efficiency.
Keywords: cycloisomerization; cobalt-catalyzed; pyrrolidine; N,N-diallylaniline; phenanthroline ligand